System To Support The Survey Of GIS Use Within The Business Sector - Zaharin, Marzuki Matt (1995)
A survey will be conducted on September 1995 regarding the GIS use within the business sector. A system is consider to be able to help the analyser to evaluate the questionnaires in term of inputting data, analyses and report. The developments of the system are solely base on the questionnaires itself. Much effort have been put towards the analysis part. Eventhough the system did functions but it did not cover all the aspect necessary for the analysis part. This analysis is trying to gather the raw data to be represented into a graph for clarity in understanding.